Evaluation of Flexural Strength and Vickers Micro Hardness of Three Different Denture Base Resin Materials - Mohammed Ibrahim Mathar; Manish Chadha; AlMoataz Mohamed Amin Soliman; Saif H. Alharbi; R. Murali Karthik; Mohammed Ziauddeen Mustafa (Journal of Pharmacy and Bioallied Sciences)
Objectives: To evaluate the Vickers hardness and flexural strength of computer-aided design/computer-aided manufacture (CAD/CAM) milled, 3D-printed, and traditional heat-polymerized denture base resins used in computer-aided design and manufacture. Materials and Methods: A total of 60 samples were fabricated from CAD/CAM milled resin (PMMA dental material-Ruthinium disc, Badia Polesine (Rovigo) Italy), CAD/CAM 3D-printed resin (NextDent Denture 3D+, Soesterberg, The Netherlands) and conventional heat-polymerized (HP) denture base resin (DBR) (Triplex hot Ivoclar-Vivadent, Liechtenstein). Based on the three different denture base resin materials (n = 10/material) (30/flexural strength and 30/microhardness), the samples were split into six groups. The 3-point bending test was used to assess flexural strength, while Vickers microhardness test was used to assess surface hardness. The acquired data was statistically assessed. Results: CAD/CAM milled resins showed appreciably greater values for both the flexural strength and surface hardness, followed by conventional HP denture base resin and CAD/CAM 3D-printed resin. Pairwise comparison for Flexural Strength and Vickers microhardness revealed significant differences between groups. Conclusion: CAD/CAM milled resins had the highest surface hardness and flexural strength compared to Conventional HP denture base resin and CAD/CAM 3D-printed resin.